A Study of a Nonlinear Ordinary Differential Equation in Modular Function Spaces Endowed with a Graph. (30th January 2021) - Jeddi, Jaauad; Kabil, Mustapha; Lazaiz, Samih
Abstract : In this paper, we prove by means of a fixed-point theorem an existence result of the Cauchy problem associated to an ordinary differential equation in modular function spaces endowed with a reflexive convex digraph.